Power Changes Inside and Outside the Palace with the Power of the Emperor Balance in the Middle and late Western Han Dynasty - Qi, En (Journal of Social Science and Humanities, 2025)
In the early Western Han Dynasty, the prime minister had a great influence in the upper bureaucratic system because of the respect for his position and the broad authority. At this time, the emperor’s measures were easily restricted by the prime minister. In order to strengthen the imperial power, Emperor Wu of the Han Dynasty set up the inner court to distinguish and balance the outer court represented by the prime minister. The division of internal and external dynasties appeared for the first time in the upper bureaucratic system of the empire. At the beginning of the establishment of the inner dynasty, it was always located in the center of the upper power. Correspondingly, the prime minister gradually evolved into an executive body, losing the power to participate in decision-making. With the replacement of the emperors in the middle and late Western Han Dynasty, the power distribution between the internal and external dynasties was not fixed, and the overall trend was that the internal dynasty was strong and the external dynasty was weak. Only after the destruction of the Huo’s group, the long-weakened foreign dynasty was restored to some extent. At this time, the powerful eunuch became a third-party force that restricted the internal and external dynasties. The secondary combination of the foreign relatives and the internal dynasties made the distribution of power in the upper class of the empire usher in a new turning point. The emergence of these new forces and new changes is the embodiment of the imperial power balance. The emperor manipulated the multi-party forces of the upper class of the empire to achieve a relative balance of power.